2019
DOI: 10.21153/jtlge2019vol10no1art792
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing learning outcomes from industry engagement in Australian engineering education

Abstract: Industry engagement, commonly implemented as a 12 week industry placement during a vacation towards the end of the degree, has traditionally been a provider-mandated component of externally accredited professional engineering degrees in Australia. Such placements are intended to bridge knowledge and capability gaps between academic study and engineering employment and contextualise the final phase of academic study. Changes in the composition of Australia’s engineering industries have made it progressively har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…As a programme that allowed academics, students, and industry to come together, the information and knowledge exchange and learning experiences obtained during the virtual symposium had benefitted all parties involved. Since placement and internships are getting more complex due to various changes in the industry and global issues, in-curricular engagement through electronic and virtual communications might be the way forward for both academia and industry (Male & King, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a programme that allowed academics, students, and industry to come together, the information and knowledge exchange and learning experiences obtained during the virtual symposium had benefitted all parties involved. Since placement and internships are getting more complex due to various changes in the industry and global issues, in-curricular engagement through electronic and virtual communications might be the way forward for both academia and industry (Male & King, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, students gain realworld knowledge and experience through engagement activities such as inviting guest speakers, virtual site tours, case studies and others (Burns & Chopra, 2017). Male and King (2019) found that students who engage in industry placements through workplace-based activities acquired a lot of effective and positive experiences, but acknowledged through students' responses that currently, it is not easy to get quality industry placements. Therefore, a combination of a well-constructed in-curriculum and extracurricular activities such as online interviews with experts, simulated workplace communication with experts, and authentic project-based tasks connected through virtual reality may allow for an alternate way to provide workplace and real-world experiences to the students (Male & King, 2019).…”
Section: Industry Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Many Australian universities and institutes of higher education have opted to make the engineering students responsible for acquiring 12 weeks of industry placement in order to address mandated requirements of WIL by EA (Male and King, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Despite being instrumental in equipping new engineering graduates with the much-needed employability skills and bridging the skill gap, WIL comes with its own set of challenges. Several factors including privatisation of previously state-owned engineering infrastructure, engineering-based manufacturing moving offshore, and rise in contract-based engineering services require arduous efforts in availing traditional work experience placement (Male and King, 2019). This not only delays graduation but also fails to satisfy an ever-increasing demand of employable engineering graduates and ends up accentuating the skill shortage.…”
Section: Introductionmentioning
confidence: 99%